2022
DOI: 10.17159/sajs.2022/9357
|View full text |Cite
|
Sign up to set email alerts
|

Towards medicinal tea from untapped Namibian Ganoderma: Phenolics and in vitro antioxidant activity of wild and cultivated mushrooms

Abstract: Ganoderma is a genus of mushrooms that is prized in developed nations, especially those in Asia, due to its health-promoting properties, which are attributed to bioactive compounds such as phenolics. However, in developing countries, particularly in Africa, Ganoderma mushrooms are untapped and are barely identified. In this study, we identified Ganoderma species collected from different host trees in the wild in Namibia, cultivated them on one substrate and determined their water absorption and solubility indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…The difference in that case was that the mushroom material was not wild but from mycelial cultures. The results of recent studies confirm the aforementioned conclusion [ 49 , 50 ]. Furthermore, it has also been reported that the freshness (i.e., fresh or dry) of the mushroom material plays a key role in the amounts of bioactive components recovered [ 51 ].…”
Section: Discussionsupporting
confidence: 82%
“…The difference in that case was that the mushroom material was not wild but from mycelial cultures. The results of recent studies confirm the aforementioned conclusion [ 49 , 50 ]. Furthermore, it has also been reported that the freshness (i.e., fresh or dry) of the mushroom material plays a key role in the amounts of bioactive components recovered [ 51 ].…”
Section: Discussionsupporting
confidence: 82%
“…The reported bioactivities include antibacterial, antidiabetic, antifungal, antihypercholesterolemial, antioxidant, antiparasitic, antitumor, antiviral, cardiovascular, hepatoprotective, immunomodulatory and radical scavenging effects (Hyde et al 2019;Zeb and Lee 2021;Niego et al 2021). The bioactive principles causative for those effects are polysaccharides, proteins (El Enshasy and Hatti-Kaul 2013), glycoproteins (Cohen et al 2014), phenolic compounds (Gupta et al 2018;Hamwenye et al 2022), ergosterol (Diallo et al 2020) and other terpenoids, or unsaturated fatty acids (Galappaththi et al 2022). The health-promoting properties of many fungi are the driving force for increasing their market value and incorporation into the nutraceutical industry (Niego et al 2021).…”
Section: Functional Food and Nutraceuticalsmentioning
confidence: 99%